Annotated checklist of Collembola of Nepal - Budha, Prem Bahadur; Shrestha, Pratistha (Nepalese Journal of Zoology, 2021)
This is the first annotated checklist of Collembola species of Nepal. It includes 167 collembolan species belonging to 78 genera and 17 families including 45 endemic species. Majority of the Nepalese collembolan species were reported from major trekking routes viz. Mount Everest, Annapurna Conservation Area and Langtang area with very few other locations. The highest record of collembola in Nepal is about 5800 m asl. Southern Terai and Siwalik range remain unexplored.